Criteria for Identifying Adjectival Participles in Lithuanian - Jancaitė, Laima (Taikomoji kalbotyra, 2023)
The aim of this paper is to present criteria for identifying adjectival Lithuanian participles, which function as adjectives but have participial forms, and to explain how adjectival participles can be identified through corpus data analysis. The relevance of the research lies in the fact that adjectival participles are considered as adjectives in dictionaries. Moreover, the devised identification criteria may be of added value for part-of-speech tagging, teaching Lithuanian, and other related domains.The article examines the concept of adjectivization, proposing a potential classification of Lithuanian participles based on the extent of their adjectivization (i.e., fully adjectival and partially adjectival participles). It also suggests criteria for identifying adjectival participles. The criteria, categorized into grammatical, semantic, derivational, and quantitative, are distinguished based on prior research and a pilot study. The data for the pilot study was extracted from Mokomasis lietuvių kalbos vartosenos leksikonas (The Lexical Database of Lithuanian Language Usage), encompassing 200 most frequent verbs and 49 adjectives with participial forms analyzed across two Lithuanian corpora. In addition, the order of criteria application is demonstrated in the present paper. In total, 185 frequent verbs were analyzed in the corpora to identify adjectival participles based on the following parameters: (1) the inclination of the participle to form an adverb with the suffix -ai; (2) its propensity to generate comparative and superlative forms and be used with adverbs of measure/degree; and (3) its inclination to be used attributively without verbal arguments. Methodologically, a quantitative approach was applied to analyze the data (only frequent participle forms were examined, as it is hypothesized that particularly frequent participles are adjectival).The results show that the proposed criteria, along with quantitative information, aid in the identification of adjectival participles. Seventeen identified participles are classified as separate words rather than verbal forms by Bendrinės lietuvių kalbos žodynas (The Dictionary of the Standard Lithuanian Language); one identified participle is categorized as an adjective by Lietuvių kalbos žodynas (The Lithuanian Language Dictionary); one identified participle was found to be adjectival, and another participle was used as a pronoun, while eight identified participles are considered partly adjectival. Six identified participles should not be considered adjectival. Thus, it appears that additional criteria need to be applied, and the methodology requires refinement for a more accurate identification of adjectival participles.
Keywords: adjectival participles; adjectivization; grammar; he Lithuanian language; corpus linguistics